DEVELOPING TEACHING GUIDES FOR BIOLOGY-BASED COURSES: INTEGRATING PROJECT-BASED LEARNING, CASE STUDIES, AND 21ST CENTURY SKILLS FOR PRE-SERVICE TEACHERS - Nurlaelah, Ilah; Handayani, Handayani; Lismaya, Lilis; Hayat, M. Syaipul; Druken, Bridget (EDUSAINS, 2024)
This study aims to develop teaching guides for biology-based courses, including Microbiology, Plant Anatomy, and Agribusiness, designed for pre-service teachers. These guides integrate project-based learning and case studies to cultivate 21st-century skills. Using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation) within a Research and Development (R&D) framework, the guides were systematically developed and evaluated. Results show high feasibility, with average scores of 97% for content appropriateness, 95% for presentation quality, and 100% for language clarity, demonstrating their validity, practicality, and effectiveness.